Biologi dan neraca kehidupan ulat grayak jagung, Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) pada tongkol jagung muda (Zea mays Linn.) sebagai pakan alternatif: Biology and life table of fall armyworm, Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) on baby corn (Zea mays Linn.) as alternative feed - Sumaryati, Bety; Sartiami, Dewi; Santoso, Sugeng (Jurnal Entomologi Indonesia, 2023)
Mass rearing techniques for the production of Spodoptera frugiperda larvae in large quantities as research materials is important to be developed. Baby corn has the potential to be observed as alternative feed for mass rearing of fall armyworms. However, the biology and life table of S. frugiperda feeding on baby corn has not been studied. This research aims to study the morphology, biology, and life table of S. frugiperda fed on baby corn. Larvae of F1 fall armyworm were reared singly and fed with baby corn, after pupation it was moved to containers. Thirty pairs of adults were reared in a cage filled maize plant. Observations conducted daily from the eggs until the adult died. Results showed variations in the color and size of the eggs, larvae, pupae, and adults. Developmental periods of eggs, larvae, and pre-pupae were 2.47, 14.96, and 1.83l days. Pupal period was 9.75 days (male) and 8.81 days (female). The life cycle were 37.69 days (male), and 37.7 days (female). Duration of pre-oviposition, oviposition, post-oviposition were 1.60, 7.90, and 2.26 days. Adult longevity was 11.34 days (male) and 11.76 days (female). The average number of eggs laid was 1.365,86/female with a hatch rate of 94,68%. Survival curve of S. frugiperda was type I, with GRR  of 1.442,49 individuals/generations, and  the Ro was 1.342,77 individuals/females/generation. Ther was 0.23 individual/female/day, the T  was 31.23 days, and the DT was 3.01 days. This result showed that baby corn can be an alternative feed for mass rearing of S. frugiperda.